Blue organic light-emitting diodes based on pyrazoline phenyl derivative - Stakhira, P. (2013)
The results of an experimental study of the electroluminescent device made of ITO/CuI/2,6-di-tert.-butyl-4-(2,5-diphenyl-3,4-dihydro-2H-pyrazol-3-yl)-phenol (HPhP)/3,6-Di(9-carbazolyl)-9-(2-ethylhexyl) carbazole (TCz1)/Ca:Al with efficacy up to 10.63 cd/A are presented. HPhP provides blue emission with a peak wavelength at 445 nm. The layer of TCz1 acts as an electron-transporting layer. In the framework of density functional theory (DFT) approach the geometry configuration and energy levels of HPhP are found being in a good agreement with spectral and cyclic voltammogram data.